2022
DOI: 10.1002/smtd.202200664
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Porous Cellulosic Triboelectric Materials for Extreme Environmental Conditions

Abstract: advanced materials with natural hierarchical structures have attracted considerable attention from researchers. [18][19][20][21][22][23][24] As an inexhaustible and sustainable resource, biomass materials show advantages in the development of highperformance structural materials due to their special hierarchical and porous structure. [25][26][27][28][29] The highly ordered hierarchical structure provides strong mechanical support for plant growth and promotes the vertical transportation of nutrients. The natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Seven major microplastic components were detected in the water samples from the inlet rivers with significant differences between component groups and with POM accounting for the highest percentage at 34.66% and silicone accounting for the lowest at 2.23%; the results were as follows: POM (34.66%) > PU (29.49%) > ALK (13.37%) > PE (5.46%) > PET (5.15%) > PVC (2.59%) > silicone (2.23%) (Supplement Figure 5). The results indicate that POM and PU make up the major part of the microplastic composition, and these two components are mainly used in industrial and agricultural production. , The sources of the different microplastic fractions in the water bodies flowing into Taihu Lake also vary slightly. Figure a shows that the sources of PVC, POM, PU, and PET in the water bodies are more homogeneous, while the silicone resin in the water bodies flowing into the rivers of Taihu Lake mainly originates from Caoqiao River, PE mainly originates from Dapu Port, and ALK mainly originates from Wujin Port.…”
Section: Resultsmentioning
confidence: 98%
“…Seven major microplastic components were detected in the water samples from the inlet rivers with significant differences between component groups and with POM accounting for the highest percentage at 34.66% and silicone accounting for the lowest at 2.23%; the results were as follows: POM (34.66%) > PU (29.49%) > ALK (13.37%) > PE (5.46%) > PET (5.15%) > PVC (2.59%) > silicone (2.23%) (Supplement Figure 5). The results indicate that POM and PU make up the major part of the microplastic composition, and these two components are mainly used in industrial and agricultural production. , The sources of the different microplastic fractions in the water bodies flowing into Taihu Lake also vary slightly. Figure a shows that the sources of PVC, POM, PU, and PET in the water bodies are more homogeneous, while the silicone resin in the water bodies flowing into the rivers of Taihu Lake mainly originates from Caoqiao River, PE mainly originates from Dapu Port, and ALK mainly originates from Wujin Port.…”
Section: Resultsmentioning
confidence: 98%
“…Reproduced with permission. [ 238 ] Copyright 2022, Wiley‐VCH. e) The network structure in the cellulose paper facilitates the loading of PEI.…”
Section: Strategies For Dielectric Modulation Of Cellulosic Triboelec...mentioning
confidence: 99%
“…[236] The cellulose network structure formed by the interwoven fibers can increase the filler loading. [237] Inspired by natural bamboo, Zhao et al [238] prepared a unique bamboo/polyaniline (PANI) triboelectric material with a hierarchical porous structure (Figure 9d). The hierarchical porous structure provides a template for the construction of 3D conductive networks, enhancing the triboelectric properties of the material and enabling it to maintain stable and efficient power output in extreme environments.…”
Section: Structural Design For Dielectric Modulation Of Cellulosic Tr...mentioning
confidence: 99%
“…[21,99] Cellulose is a biopolymer that decomposes at high temperatures but generally has good thermal stability at temperatures of 300 °C. [100] Zhao et al [101] reported the production of triboelectric materials with special nanostructures from natural bamboo, demonstrating that the materials maintain high stability under extreme environments such as high temperature (200 °C), low temperature (−196 °C), and combustion environment. The research provides new research ideas for the construction and application of biomass structured materials under extreme environmental conditions.…”
Section: Other Characteristicsmentioning
confidence: 99%